DETERMINAN PERILAKU YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS SEBA KECAMATAN SABU BARAT KABUPATEN SABU RAIJUA - Betruida Ratu Djia; Marni, Eryc Z. Haba Bunga (CV. Adiba Aisha Amira, 2025)
Seba Health Center is one of the health centers located in West Sabu sub-district, Sabu Raijua Regency. Diarrhea is the main cause of morbidity and mortality in children under five in the world. Every year there are 525,000 cases of children under five dying due to diarrhea. There are several factors that can increase the risk of toddlers experiencing diarrhea, including: Mother's knowledge, education, work, motivation, and environment. This study aims to analyze the relationship between behavioral determinants related to the incidence of diarrhea in toddlers in the Seba Community Health Center Working Area, West Sabu District, Sabu Raijua Regency. This type of research is observational with a cross-sectional design. The sample in the study was 56 cases. The sampling technique in this research is simple random sampling. The data analysis used is Univariate and Bivariate analysis. Data were analyzed using the square test with a significance level of ɑ=0.05. Based on the research results, it shows that there is a significant relationship between Knowledge (p=0.004), Work, (p=0.033), Education (p=0.047), Motivation (p=0.011), Environment (p=0.022). Community Health Centers can provide education about the importance of preventing diarrhea by going directly to Posyandu and increasing information media.